A Prospective study on Impact of Gestational Diabetes Mellitus (GDM) Management on Burden of Diabetes mellitus (DM) in Uttar Pradesh India - Rajesh Jain; Sanjeev Davey; Susanne Olejas; Rachna Jain (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Gestational diabetes mellitus (GDM) is a type of glucose intolerance which is often identified first time in pregnancy. It is important to assess whether in Uttar Pradesh (a largest state of India with one of the highest rate of the infant and maternal mortality rate has also higher chances of future Diabetes Mellitus (FDM) in mothers which may attribute it to GDM uncontrolled in pregnancy. The Primary objective of this study was to be determine whether the future Diabetes Mellitus in women is associated with GDM degree of control and can the GDM Management in Pregnancy Improves future Diabetes Mellitus via a Prospective study approach. A prospective cohort study was done for 2 and half years from October 1, 2016, to March 31, 2019, at 900 GDM screening units as a part of the Gestational Diabetes Prevention and Control Project, Uttar Pradesh approved by the Indian Government in the state of Uttar Pradesh, India. A total of 515532 pregnant women were screened during their 16-32th weeks of pregnancy by impaired oral glucose test (OGTT) as per NHM Guidelines for GDM, 12784 GDM & 7287 Non GDM for maternal and perinatal outcomes were followed up in both GDM and non GDM categories in the 2 years and 6 months (2016-2019) after blood sugar management. The Pregnant women were recruited at 900 healthcare facilities, 515532 Pregnant Women have been screened at 16-20 Weeks & 24th-28 weeks of pregnancy as per Guidelines of National health Mission, GOI Guideline. There were not only Significant( p< 0.0001) Perinatal deaths(597)4.6% in GDM category as compared to Non GDM category139(1.9%). There were also more future Diabetics in women in GDM cases, with High Birth weight Babies specially in less Control of Blood Sugar levels during Pregnancy. The Overall incidence of future Diabetes in women cases were only 15.9% in GDM Cases at 140-160 mg/dl at GDM Diagnosis,but as the blood sugar levels increased the Incidence of future diabetes in women increased to high level[>160-200mg/dl (36%)]. So there was a significant association between GDM in Mothers and women developing Diabetes after delivery early with poor perinatal & neonatal outcomes, which suggests GDM Management is Crucial in pregnancy for reducing burden of prospective diabetes in Indian women.